DUKUNGAN SUAMI TERHADAP PARENTING SELF EFFICACY PADA IBU POSTPARTUM DENGAN SECTIO CAESAREA - Diah Astutiningrum; Yetty Bayuana; Herniyatun (Stikes Muhammadiyah Klaten, 2021)
Background, The postpartum period requires an adjustment or adaptation process, this period is a crisis situation for mothers, partners and families due to various changes that occur physically, psychologically, and family structures. Delivery with Sectio Caesarea (SC) also requires an adaptation process that is not easy for postpartum mothers.Purpose, To determine the relationship of husband's support to parenting self-efficacy in postpartum with sectio caesareaMethods This research method uses descriptive quantitative research methods with a cross sectional approach. The number of samples is 40 respondents. The measuring instrument used is a questionnaire. Data analysis used statistical test with Spearman rank test.The results showed that 1 respondent (2.5%) with high parenting self-efficacy received less support from their husband, 19 respondents (47.5%) with high parenting self-efficacy and 2 respondents (5.0%) with parenting. Low self-efficacy received sufficient husband support while 18 respondents (45.0%) with high parenting self-efficacy received very supportive husband support.In conclusion, husband's support has a relationship with the level of parenting self-efficacy in postpartum with sectio caesarea (p value = 0.009 < 0.05).Recommendation, Future researchers are expected to be able to conduct further research related to other factors that affect parenting self-efficacy in postpartum mothers with sectio caesarea so that the most significant factors that affect parenting self-efficacy can be identified.